Neonatal cholestasis - Single centre experience in Central India - Mayank Jain; Sagar Adkar; Chandrashekhar Waghmare; Jenisha Jain; Shikhar Jain; Kamna Jain; Gouri Rao Passi; Rashmi Shad Vinay; M K Soni (Wolters Kluwer Medknow Publications, 2016)
Background: Neonatal cholestasis syndrome (NCS) is a major cause of morbidity and mortality in infants. The disorder has rarely been studied in centers from Central India. Objectives: To study the prevalence, clinical presentation and etiology of NCS at a tertiary referral center in Central India. Materials and Methods: The study was carried out at a tertiary referral center in Central India. The study is a descriptive study. The records of all patients with suspected NCS treated in the Department of Pediatrics from 2007−2012 were analyzed. Results: One hundred and sixty-eight children had a provisional diagnosis of NCS. The complete records of 100 children were available for the study. The median age of presentation was 78 days (range 15−270 days). The male: female ratio was 1.17:1. The clinical features noted were- jaundice (100/100,100%), failure to thrive (73,73%), organomegaly (68, 68%), acholic stools (38,38%), abdominal distention (52,52%) and poor feeding (29, 29%). The etiology as confirmed by investigations is as follows- neonatal hepatitis (20,20%), idiopathic neonatal hepatitis (18,18%), biliary atresia (41,41%), sepsis (14,14%) and others (7,7%). Conclusions: The proportion of NCS in our group of patients was 1.2 per 1000 patients. Jaundice, organomegaly and failure to thrive are the common presentations. Biliary atresia, neonatal hepatitis and idiopathic neonatal hepatitis were the common etiological factors at our center.